Effect of Date Juice and Coconut Water on Hemoglobin (Hb) Levels in Anemia Gravidarum - Mufliha, Ayu Laila; Dinengsih, Sri (Jurnal MIDPRO, 2023)
Anemia is something condition where amount cell blood red or hemoglobin concentration in it more low from usually. Deep anemia pregnancy is condition mother with hemoglobin levels (Hemoglobin) in blood more low from 11 gr/dl. Knowing influence giving juice dates (Phoenix dactylifera .L ) and coconut water (Coconut water) against mother's hemoglobin ( Hb ) level pregnant with anemia trimester III at the health center babelan. This study use Quasi experiment with pretest- posttest with control group design. Taking sample done use technique purposive sampling amounted to 34 mothers third trimester of pregnancy consisting of 17 people group intervention and 17 person groups control. Instrument study is form sheet observation, informed consent, date juice drink and coconut water data analysis used descriptive statistics and paired t-test to know difference score before and after intervention. There is difference average rate hemoglobin pretest and posttest given juice dates Phoenix dactylifera .l ) and water coconut Â (Coconut water) with paired t-test results obtained Value 0.000 (p <0.05). There is influence gift juice dates (Phoenix dactylifera .l) and water coconut (Coconut water) to rate hemoglobin ( Hb ) mother pregnant with anemia trimester III at the health center babelan 2023. Expected drink dates (Phoenix dactylifera .l ) and water coconut (Coconut water).It can be one choice non-pharmacological drugs in increase hemoglobin level on mother pregnant trimester III.